Analisis Yuridis Ketentuan Penanaman Modal Asing Atas Alih Teknologi terhadap Peningkatan Kesejahteraan Tenaga Kerja dalam Negeri - Wanda Natagaul; Muhammad Iswan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The total foreign investment still dominates the overall investment’in Indonesia. The’substantial’amount of’foreign‘investment’in Indonesia represents a significant opportunity to enhance the knowledge and technological utilization capabilities of domestic labor. Improving the quality of domestic labor’is essential for’advancing’the well-being of the’society. This research aims to analyze the provisions regarding technology’transfer in the’Investment Law and the’role of’technology transfer’in enhancing the welfare of domestic labor. This study is of the normative juridical type with a conceptual approach. The research findings indicate that the Investment Law has regulated the obligations of investors, including foreign investors, to transfer technology to domestic labor. Technology transfer’plays a crucial role in’striving for the’welfare’of domestic labor. The’researcher found that the provisions regarding technology transfer in the Investment Law are inconsistent because the obligation to transfer technology is not accompanied by strict sanctions for investors who fail to transfer technology to domestic labor.